Facilitating the high-quality agricultural development with digital economy: a panel data study of Jiangsu Province from 2013 to 2021 - Ma, Xiaoxu; Lv, Lianzhou (Frontiers in Sustainable Food Systems, 2024)
Agricultural modernization can only be attained through the high-quality development of agriculture, which is made possible by the deep integration of the digital economy with traditional agriculture. From the perspective of the entire agricultural industry chain, this paper offers a theoretical and empirical examination of the digital economy’s role in enabling high-quality agricultural development. The fixed effects model, convergence test, threshold model, and spatial error model were implemented based on the panel data of 13 cities in Jiangsu Province from 2013 to 2021 to validate the role of the digital economy in enabling high-quality agricultural development. The findings indicated that first, for every 1% increased in the level of digital economy development, the level of high-quality agricultural development increased by approximately 0.183%. Second, the high-quality development of agriculture had the characteristics of absolute convergence and conditional convergence, and there was a non-linear character in the role of the digital economy in the high-quality agricultural development. Third, for every 1% increase in the development level of digital inclusive finance, the level of high-quality agricultural development in surrounding areas with similar economic levels will be improved by about 0.188%.In this regard, Jiangsu Province should grasp the opportunity of the era of digital economic development, continue to strengthen the construction of digital economic development in backward areas, and attach great importance to inter-regional exchanges and cooperation in the construction of digital agriculture.